THE IMPORTANCE OF SOME IODINE-CONTAINING PLANTS FOR THE PREVENTION OF IODINE DEFICIENCY AND THEIR ANTIBACTERIAL AND CYTOSTATIC ACTIVITY - Megainska Anna; Strashko Stanislav; Bilyk Zhanna; Bilyk Valentina; Kuts Valeriia (World Science, 2022)
One of the urgent problems of health care in Ukraine is the problem of iodine deficiency, which is solved by creating special foods. The least harmful component of this diet may be plant ingredients. Therefore, the study of plants rich in organic iodine compounds is an important task of medical botany. The paper presents the results of the study of iodine-enriching, antibacterial and cytostatic activity of Lemna minor L., Zostera marina L., Laminaria saccharina L., Xanthium strumarium L. It is shown that all the studied plants have an iodine-enriching effect, but the most effective is Xanthium strumarium. All studied plants showed antimicrobial activity, but no direct correlation between iodine content and antimicrobial activity was found. The antibacterial activity of Xanthium strumarium against Escherichia coli exceeds the similar effect of antibiotics such as cefazolin and ampicillin, and against Staphylococcus aureus is equal to the effect of norfloxacin. Xanthium strumarium and Lemna minor showed fungicidal activity against Candida albicans. The greatest antitumor activity is characteristic of Laminaria saccharina, Xanthium strumarium Zostera marina. The expediency of using the studied plants in the conditions of iodine deficiency is discussed.